Wage subsidies targeted to jobseekers with disabilities: Subsequent employment and disability retirement - Nikolay Angelov; Marcus Eliason (IZA Journal of Labor Policy, 2018)
In many countries, a non-negligible percentage of the working-age population has impairments that also entail reduced work capacity, and disability retirement is increasing. Despite this, studies on the effects of policies aimed at enhancing the labour market inclusion among people with disabilities, such as targeted wage subsidies, are surprisingly few. In an attempt to fill this gap, we have studied how wage subsidies affect future labour market outcomes for jobseekers with disabilities, in terms of employment and disability retirement. By using inverse probability weighting applied to rich Swedish register data, we contrast participants in the wage subsidy program to observably similar non-participants during a 19-year period. We find that participation was associated with both positive and negative labour market outcomes. On the negative side, participants were less likely to have unsubsidised employment. On the positive side, leaving the labour market through the disability insurance program was somewhat less common among participants. Moreover, using a broader employment measure including subsidised jobs, the participants were found to be employed to a larger extent, which could be interpreted either as locking-in effects or as fostering labour market inclusion.
Keywords: C21; J14; J23; 330; Disability; Wage subsidies; Subsidised employment; Disability insurance; Labour market programs